2009
DOI: 10.1002/app.31068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clay dispersion on the synergism between clay and intumescent flame retardants in polystyrene

Abstract: Different formulations were designed to evaluate the effect of organically modified clay (DK4) on the combustion behavior of polystyrene (PS) containing an intumescent flame retardant, poly(4,4-diaminodiphenyl methane spirocyclic pentaerythritol bisphosphonate) (PDSPB). The results of transmission electron microscopy reveal that DK4 selectively dispersed in the PDSPB phase. An investigation of thermogravimetric analysis revealed that the thermal stability of PS resin showed no obvious change with the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The nanoplatelet of ZrP cannot efficiently insulate the underlying material and slow the escape of the volatile products [30]. Meanwhile, inter-chain bridges would be induced by the presence of Zr 4+ and accelerate the cure reaction of the IFR compositions, which means that the solidification processes cannot be synchronous with the elimination of gaseous products to give the intumescence and form the multicellular structure [31].…”
mentioning
confidence: 99%
“…The nanoplatelet of ZrP cannot efficiently insulate the underlying material and slow the escape of the volatile products [30]. Meanwhile, inter-chain bridges would be induced by the presence of Zr 4+ and accelerate the cure reaction of the IFR compositions, which means that the solidification processes cannot be synchronous with the elimination of gaseous products to give the intumescence and form the multicellular structure [31].…”
mentioning
confidence: 99%
“…The nanoscale dispersion of the montmorillonite in the polymer is of utmost importance, as the type of dispersion determines the mechanical and thermal properties of the nanocomposites [21]. Previous work on vinyl ester resins by Gilman et al showed that vinyl ester nanocomposites mixed for 10 min results in the formation of intercalated structures [23,24].…”
Section: Dispersion Of Montmorillonitementioning
confidence: 99%
“…Previous study showed that the addition of organically modified clay into HDPE/EVA with ammonium polyphosphate (APP) and other charring agents could improve thermal stability, as well as reduction in peak heat release rate [20]. However, unlike the synergism between montmorillonite and low molecular weight IFRs, the synergism between polymeric IFRs and montmorillonite is largely affected by the distribution of montmorillonite due to the multiphase structure of such a system [21].…”
Section: Introductionmentioning
confidence: 99%
“…The combustion behavior and flame retarded mechanism are especially focused on [93][94][95][96][97][98]. In the study of multiphase and multicomponent copolymer ABS/clay nanocomposite, clay can intercalate uniformly into multiphase of ABS by balancing the polarity of butadiene (by grafting maleic anhydride) and acrylonitrile-styrene phase, as shown in Figure 2.…”
Section: Flame Retarded Polymer Nanocomposites 21 Flame Retarded Polmentioning
confidence: 99%